Effect of sinapic acid on memory deficits and neuronal degeneration induced by intracerebroventricular administration of streptozotocin in rats - Shahmohamady, Pouneh; Eidi, Akram; Mortazavi, Pejman; Panahi, Negar; Minai-Tehrani, Dariush (Polish Journal of Pathology, 2018)
The present study aimed to elucidate the neuroprotective effect of sinapic acid on intracerebroventricular streptozotocin (ICV-STZ) induced neuronal loss and memory impairment. To test this hypothesis, male Wistar rats were randomly divided into 11 groups: normal control, sham-operated control, sinapic acid (2.5, 5, 10, and 20 mg/kg bw intragastrically, daily) alone, Alzheimer control rats (ICV-STZ, 3 mg/kg bw), sinapic acid (2.5, 5, 10, and 20 mg/kg bw intragastrically, daily) together with STZ, and the treatment was performed accordingly. After 28 days of ICV-STZ administration, the animals were assessed for cognitive performance using passive avoidance test and then sacrificed for biochemical and histopathological examinations. Sinapic acid was found to be effective in improving antioxidant status and preventing memory loss in Alzheimer rats. Moreover, TNF-α level in the hippocampus was significantly decreased by sinapic acid. Also, administration of sinapic acid significantly increased the levels of antioxidant enzymes and decreased malondialdehyde level in the hippocampus. Histopathological examination showed that sinapic acid reduced cell loss in the cerebral cortex and hippocampus in Alzheimer’s rats. The present study suggests that sinapic acid is effective in the prevention of memory loss and improvement of oxidative stress and might be beneficial in the treatment of Alzheimer’s disease.